Wuhan, 1938 : war, refugees, and the making of modern China - MacKinnon, Stephen R. (University of California Press, 2008)
During 1938, a flood of Chinese refugees displaced by the Anti-Japanese War (1937-1945) converged on the central Yangzi valley tricity complex of Wuhan. This text tells the full story of Wuhan's defense and fall, and how the siege's aftermath led to new directions in the history of modern Chinese culture society, and politis.